GREEN SKILLS: A NEW DEVELOPING DIRECTION IN THE LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The study explores how the visibility of environmentally damaging practices or "green skills" can play a critical role in promoting local economic development and overall economic growth. Green skills enhance job creation, competitiveness, economic diversification and productivity by incorporating technical, transversal and managerial competencies that support sustainable practices in various sectors. The Economic Benefits of Green Skills examines the impact of integrating skills into the workforce on the growth of the green economy. Despite their advantages, there are challenges such as skills gaps and inadequate training programs. The study emphasizes the need for policy frameworks, updated education curricula and public awareness to develop these skills. Also, the author studied the difficulties and shortcomings in the promotion of green skills and made tables. This study was conducted by linking labor market skills and jobs to the green economy. The research was analyzed using information from reliable, official global and local organizations.
Keywords: Green economy, green jobs, green skills, environment, skills, capability.